Was bedeutet ärztliche Professionalität? - Kühlein, Thomas (Zeitschrift für Allgemeinmedizin, 2020)
There is a tacit contract between medicine and society. The essence of this contract is professionalism. But while most physicians know the rules of professional behavior towards the patient by the Declaration of Geneva, few know those towards society. This is why the topic of the 53. Conference of the German College of General Practitioners and Family Physicians (DEGAM) in Erlangen was chosen to be “The work of the general practitioner between patient welfare and claims of society – What does medical professionalism mean?” This article relates to the keynote lecture held at the beginning of the conference.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Conference of the German College of General Practitioners and Family Physicians (DEGAM); Family physician; Keynote; Professionalism; Society